Artistic the work to the winter preparation (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
The work to the winter from entering before students artistic the work to study preparation must will be Because students work content right perception reach for life about known to the imagination have to be necessary Of this for preparation works will be held . As you know , in the classroom reading based on artistic and popular science texts stands Read the students text with introduction to study preparation from the stage starts . Preparation stage writers about information give , students in the work to be described events perception make , work to feel the pathos , stranger and a lot meaningful words are more complicated kind of figurative expressions explain such as issues own into takes If the work year seasons about if so , nature to his bosom travel organization is also in the classroom reading success to provide service does